Autodeterminação na aprendizagem musical mediada por tecnologias digitais no ensino médio: uma pesquisa-ação em uma escola estadual de Mossoró/RN - Silva, Gibson Alves Marinho da (2019)
This study aimed to understand the motivational processes of high school students in art / music classes using digital technologies, from the perspective of Self-Determination Theory (REEVE, 2006; RYAN; DECI, 2017; DECI; RYAN, 2000; DECI, 1998). From this perspective, the motivation was studied in order to understand why people perform their tasks. Motivation is influenced by intrapersonal and interpersonal factors, that is, it studies the internal and external factors that influence motivation. According to Ryan and Deci (2017, 2000a), environments in which subjects have freedom in their choices (support for autonomy) and activities are in accordance with their abilities (perception of competence), provide a social bond (feeling of belonging). To achieve our goals, we use the integral-action-research method, from André Morin (2004) perspective. Data were collected through online questionnaire, participant observation, interview - through the focus group - online interactions and filming observations. The results indicated that the students' motivation in the arts / music classes was not intrinsically motivated, but rather, extrinsically, at their more self-determined levels. However, the motivation was considered enigmatic and multifaceted. The motivation presented by the students depended heavily on the teacher's motivational style, social environment and interpersonal relationships. The applications, sites and games proposed in this study were able to promote students' basic psychological needs, as well as a viable option for teaching music in high school.